Perlindungan Pasien Terhadap Praktek Pelayanan Kesehatan Akupunktur di Kabupaten Banyumas - Muhammad Rendy Putra Pratama (UNES Law Review, 2023)
Indonesian Health Services are not only medical health services but also traditional health services. There are various types of health services in Indonesia, one of which is traditional health services, an example of which is acupuncture. Acupuncture is an alternative medical service that is chosen by the public because it is cheaper, but many acupuncture clinics have practice permits even though this is mandated in statutory regulations. This study aims to analyze the legal protection of patients and the factors that influence the registration of acupuncture practice permits. The method used is empirical juridical using primary data and secondary data. As a result, patient protection has been accommodated in applicable regulations and law enforcement of acupuncture practice is influenced by legal factors, law enforcement factors, facilities and infrastructure factors, community factors and cultural factors.